The Poles in Vienna in the literary works of Radek Knapp - Romejko, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Migration is a phenomenon accompanying humanity from its beginnings. The issue of migration is dealt with not only by scholars, but also by writers and novelists. Among them is Radek Knapp (1964-) from Warsaw, who came to Vienna at the age of twelve, and where he lives to this day. In his novels and short stories, Knapp presents the reality of Vienna and its inhabitants from the perspective of ordinary people.
Keywords: novel; Poles; Vienna; Knapp, Radek (1964- )